Pengaruh SPIP, Pemanfaatan Teknologi Informasi, dan Gaya Kepemimpinan Transformasional terhadap Kualitas Laporan Keuangan (Survei pada OPD Pemerintah Kota Cimahi) - Cynara Putri Danari; Arie Apriadi Nugraha (Indonesian Accounting Research Journal, 2025)
Financial report is a medium of accountability to report users. This study aims to determine the effect of Government's Internal Control System (SPIP), the use of information technology, and transformational leadership on the quality of financial reports. The population of this study consisted of 29 OPD in the City Government of Cimahi. This research collected data through questionnaire and observation. Respondents of this study consisted of 75 people. The data analysis method used is multiple linear regression analysis processed with the help of SPSS version 26. The results showed that the internal control system and transformational leadership style have a positive and significant effect on the quality of financial reports, while the use of information technology didn’t have a significant effect on the quality of financial reports. Government’s internal control system, the use of information technology, and transformational leadership style have simultaneous affect together to the quality of financial reports.